Teachers’ Attitude Towards Inclusive Education in Nepal (Interdisciplinary Research in Education, 2019)
This article assesses the attitude of teachers towards inclusive education by their age, gender, qualifications, training, disability and teaching experience. Under the quantitative survey design, 63 teachers from four schools participated in the study, who responded to a Likert questionnaire measuring attitude towards inclusive education. Teachers are found generally positive towards inclusive education. On a Likert scale ranging from 1 to 5(highly positive), the overall attitude of teachers is 3.32. Looking at attitude by gender, male teachers are found slightly positive towards inclusive education than female ones. Similarly, younger teachers are found positive than older teachers. Trained and experienced teachers are also found positive than untrained and inexperienced ones. In addition, teachers with some disabilities are found to have a more positive attitude than other groups of teachers.